Effects of a Logistic Reaction to Finite Difference Numerical Solutions of the Inviscid Burgers Equation - Mungkasi, Sudi (Indonesian Journal of Information Systems, 2020)
We solve the inviscid Burgers equation involving a logistic reaction. The goal is to investigate the effects of the logistic reaction to numerical solutions of the inviscid Burgers equation. We use standard and nonstandard finite difference methods. Based on our research results, the logistic reaction in the inviscid Burgers equation makes the shock wave propagates faster.